Impact of Corporate Perceived Value on Satisfaction and Loyalty among Life Insurance Policyholders in Nepal - Thapa, Bhim Kumar (Journal of Emerging Management Studies, 2024)
Purpose – The purpose of this research is to analyze the life insurance industry in Nepal from the perspective of customer satisfaction (CS) as a mediator between service quality, corporate image, trust, and loyalty (CL). Design/methodology/approach – A quantitative research design was employed for the research analysis, utilizing a structured questionnaire to collect primary data. The population consisted of all life insurance policyholders in Nepal. A purposive sampling method was used to select participants based on their experience with life insurance services. A total of 388 completed questionnaires were gathered, ensuring a diverse representation of customers across various regions. Data analysis was conducted using structural equation modeling (SEM) to test the hypothesized relationships between service quality, corporate image, trust, customer satisfaction, and customer loyalty. Findings – The results revealed that service quality, corporate image, and trust positively affect customer satisfaction, and customer satisfaction mediates the relationship between these factors and customer loyalty. The results highlight those improvements in service quality, corporate image, and trust lead to higher satisfaction, which in turn strengthens customer loyalty in the life insurance sector. Conclusion – The research concludes that life insurance companies in Nepal could focus on improving operational efficiency, building a strong business profile, and fostering confidence to enhance customer experience, which ultimately boosts customer loyalty. The mediating role of customer satisfaction is key to understanding and improving customer retention strategies in the competitive life insurance market. Implications – Life insurance companies in Nepal could focus on cultivating a positive corporate image by emphasizing transparency, ethical practices, and reliable service. These elements are essential for building customer trust and satisfaction, which directly influences loyalty. Although service quality shows an important role in customer satisfaction, companies need to understand that service quality has to align with customer expectations to drive long-term loyalty. Originality/value – The author contributed to the conceptualization of the research study, the design, the development of the survey instrument, and interpretation of the results. The research is novelty in the sense that customer loyalty has not previously explored in the Nepali life insurance sector, making this research a unique one.